SOSIALISASI PENINGKATAN KESADARAN IBU HAMIL TENTANG PENTINGNYA 1000 HARI PERTAMA KEHIDUPAN - Tata Rustandi; Eva Muti’ah; Wulan Riska Dewi; Handy Setiayadi; Wiwik Novianawati; Encu Encu; Basrowi Basrowi (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The Golden Period of a child starts from the first 1000 days of life or starts from 4 months in the womb to 2 years of age. At this time, nutritional intake and maternal health must be really considered because it determines the growth and development of children perfectly. Poor nutrition will result in the physical and brain development of children becomes inhibited.  This community service (PkM) aims to increase the literacy of mothers about the importance of the first 1000 days of life to improve the healthy lifestyle of the community. The method used in this (PkM) is the extension method. Data collection techniques through pre-test and post-test. The results (PKM) show that there are differences in counseling activities for the first 1000 days of life to improve a healthy lifestyle